(untitled) (مجلة إحالات, 2026)
Plagiarism is a deeply discussed matter. Cases of plagiarism at various levels are being spotted daily. In this regard, this study aims at examining what third-year English as a foreign language (EFL) students at the University of Mascara believe to be the causes of plagiarism. Undergraduates were asked to express their views on a short essay entitled « According to you, why do students plagiarise ? ». The most often cited reasons involved the urge to finish the work, saving time and effort, and involuntary plagiarism. Moreover, some students expected to be instructed about its negative aspects and how to avoid them.